High Rates of Exposure to Simulated Winter Storm Cues Negatively Affect White-Throated Sparrow (Zonotrichia albicollis) Energy Reserves - Boyer, Andrea C.; MacDougall-Shackleton, Scott A. (Frontiers in Ecology and Evolution, 2020)
Climate change is causing changes in weather patterns and more frequent extreme weather events. Although birds are often able to cope with and respond to inclement weather with physiological and behavioral responses, as weather events become more severe or frequent the adaptive coping responses of many species may be pushed beyond their limits. We investigated the effects of experimental recurrent inclement winter weather cues on body composition, glucocorticoid hormones, and behavior of white-throated sparrows (Zonotrichia albicollis). We used a hypobaric climatic wind tunnel to simulate storms by transiently decreasing barometric pressure and temperature, and measured behavioral responses, body composition, and baseline corticosterone levels in birds exposed, or not exposed (control), to different frequencies of simulated storms. In study 1, experimental birds were exposed to one storm per week over 9 weeks. In study 2, experimental birds were exposed to two storms per week over 12 weeks. Birds exposed to one simulated storm per week had higher fat and lean masses than control birds, with no differences in the amount of time groups spent feeding. This change in body composition suggests that birds were coping by increasing energy stores. In contrast, birds exposed to two simulated storms per week had lower fat masses compared to control birds, even though they spent more time feeding. Experimental birds in study 2 also had lower baseline corticosterone levels than controls. These changes suggest that the coping response observed in study 1 was overcome in study 2. These findings provide novel experimental evidence that birds detect and respond to changes in temperature and barometric pressure independent of other storm-related cues. One simulated storm per week resulted in potentially adaptive responses of increase mass. However, increasing the frequency of storm exposure to twice per week may exceed a physiological threshold for tolerance to which these songbirds are able to cope. These results also experimentally demonstrate that repeated exposure to inclement weather cues can directly affects birds’ energy reserves, with strong implications for survival as severe weather events continue to become more prevalent.